A gestão do processo de negociação complexa: uma avaliação da 5ª Conferência Ministerial da Organização Mundial do Comércio - OMC, em Cancun, México - Spinola, Ana Tereza Schlaepfer (2004)
The present paper has the proposal to assess the management process of complex negotiation of the 5th OMC that took place at Cancun from September 10th until the 14th , 2003. This thesis points out the problems and questions that resulted on the collapse of a possible agreement, it also suggest proposal to solve these issues. The future of OMC is uncertain and traumatic changes suffered by many countries that live under the rules of OMC shows that something at OMC will have to change, principally on the process of complex negotiation, such as the integrity of the organization to avoid having to compromise and being damaged. There were searches for answers on the analysis and assessment of the negotiation process, studying and researching the bargain positional concepts, giving full details on the negotiation process based on principIes, exploring profusely the state of art for the management of difficult conversation. This thesis also tackles the sources of conflicts and the building of coalitions such as the G20, showing the difficulty existing in the resolution of public disputes and in the use of instruments to break the impasses. We also defined theoretical instrumental, which allowed the diagnostic ofthe actual situation at OMe. It was recommend to explore the valuation of conflicts, based on justice and equitant, the best form of negotiation by principIes, of management demanding public, on the multi stakeholder dialogue and the importance of informal parallel conversation. The environment of complexity and the extensive vision that it provides to adjust the functioning of autopoietics systems.